Comparative transcriptome analysis reveal gene regulation of dormancy release in Cardiocrinum giganteum seeds induced by temperature - Li, Yefang; Li, Xuejiao; Li, Fengrong; Wang, Lele; Li, Hongling; Zhao, Yan; Guan, Wenling (Frontiers in Plant Science, 2025)
The Cardiocrinum giganteum is a bulbous plant with extremely high ornamental and economic values. The study revealed that seeds require an extended period of variable temperature stratification treatment to overcome dormancy and initiate germination, yet the molecular mechanisms underlying embryo dormancy release remain unclear. In this research, transcriptome profiles at different germination stages of seeds subjected to variable temperature stratification were systematically analyzed and compared, while the embryo length of corresponding seed samples was quantitatively measured. The results demonstrated that within the initial 60 days of stratification, the embryo scarcely grew. After 90 days of stratification, the embryo elongated conspicuously, and germination initiated at 130 days of stratification. The transcriptome sequencing outcomes demonstrated that the differentially expressed genes (DEGs) identified in the three comparative groups were predominantly associated with plant hormone signal transduction, carbohydrate metabolic pathways, and phenylpropanoid biosynthesis metabolic pathways. Notably, genes associated with auxin, abscisic acid (ABA), brassinosteroid (BR), ethylene, and gibberellin signaling pathways were significantly upregulated during the stratification period from 30 d to 60 d, while these genes exhibited varying degrees of significant differential expression from 90 d to 130 d. Multiple key enzymes in carbohydrate metabolic pathways exhibited marked upregulation after 90d of stratification. Notably, β-glucosidase (BGLU) genes associated with polysaccharide hydrolysis (Cluster-62345.33620, Cluster-62345.31435, and Cluster-62345.35688) showed 6.68-, 5.08-, and 6.85-fold upregulation, respectively, at 130 d of stratification. Concurrently, the glycolytic pathway was upregulated throughout the process. The majority of genes involved in phenylpropanoid biosynthesis, particularly those encoding peroxidases, were activated during stratification. The reliability and accuracy of 10 genes closely associated with C. giganteum seed germination were validated using RT-qPCR. The results demonstrated that plant hormone signal transduction, carbohydrate metabolism pathways, and phenylpropanoid biosynthesis collectively participate in the post-maturation development and germination processes of the embryo. The potential roles of certain genes in these developmental and germination stages require further investigation. These findings provide novel insights into the transcriptional regulatory mechanisms underlying dormancy release in C. giganteum seeds. The candidate genes identified in this study warrant functional characterization and may contribute to advancing the understanding of seed dormancy and germination in plants.